Molecular tagging of agronomic traits using simple sequence repeats: Informative markers for almond (Prunus dulcis) molecular breeding - Kadkhodaei, S.; Nekouei, M.; Shahnazari, M.; Etminani, H.; Imani, A.; Ghaderi-Zefrehei, M.; Elahy, Mina; Ariff, A. (2011)
Informative markers are the most applicable genetic information in breeding schemes. Association studies which soundly integrate molecular and morphological data are the best choice to find informative markers, particularly in crops that are limited to only one generation per year. Therefore, in the present research the associations between different morphological traits and highly polymorphic SSRs were studied to find possible informative markers for some morphological and/or agronomical traits in almond. In total, 39 morphological traits were recorded during two years among 53 almond genotypes/cultivars. Extracted almond genomic DNA was PCR-amplified using 9 pairs flanking SSRs sequences previously cloned and sequenced specifically for almond. For finding association between molecular markers and morphological traits and identification of possible informative markers, Pearson correlation and stepwise regression analysis were employed. The results revealed a significant correlation between the morphological traits and the studied microsatellite loci. A total of 141 positive markers out of 556 polymorphic bands were identified for different traits. For some of the morphological traits more than one informative marker was detected, which consequently finding their additive effects, degree of dominance and sum of the positive and negative effects need further analysis. These informative markers can be considered as postulated candidate markers for scanning the genome for related morphological (particularly agronomical) traits, mapping and finally marker assisted selection programs.